EnviRoof – A Green technology for sustainable stormwater management - Noor Suraya, Romali; Abdul Syukor, Abd Razak; Suryati, Sulaiman; Khairul Anuar, Shahid (2021)
Sustainable stormwater management is rapidly gaining acceptance in Malaysia. It is an alternative to the traditional approach which promotes on site collection and conveyance of stormwater from roof to infiltrate into the ground or collect for reuse. EnviRoof is a green roof system consist of five component layers which capable to reduce the peak runoff and improve the quality of stormwater. Two types of vegetation i.e. beach morning glory (Ipomea pes-caprae) and creeping oxeye (Wedelia Trilobata) was tested on the experimental model.